The effect of prenatal classes on pregnant women when deciding the delivery type and coping with labor pain - Kadıoğlu, Berrin Göktuğ; Çınar Tanrıverdi, Esra; Göktürk, Elif Burcu (The European Research Journal, 2020)
﻿Objectives: The purpose of the study is to determine the impacts of the prenatal classes on pregnant women while determining the type of delivery and coping with pain during delivery.Methods: This study is descriptive. It involves analysis of 247 participants that were selected as samples from a known population of 653 pregnant women who participated in prenatal classes of our hospital. The prenatal classes took place for 3 weeks and 16 hours in total. They filled the forms regarding the class activities before and after the class. The data were evaluated by using SPSS 16.0 packaged software.Results: The mean age of the pregnant women was 27.50 ± 4.60 years. The women, who had their first pregnancy, were 73.3%. Before the class, 62.8% declared that they were planning to have a vaginal delivery. The ones, who stated that they were afraid of pain, were 78.9%. In interviews after the classes, 89.5% of the participants stated that the classes affected their choice of delivery type. The rate of participants that found classes relieving for their anxiety and concerns was 94.70%. The rate of participants that had a vaginal delivery was 81.80%. The influence of the prenatal classes while determining the type of delivery was statistically significant. (p < 0.001 by Mc Nemar test).Conclusions: Participation with the prenatal class removes the anxiety of the pregnant women, encourages them to have vaginal delivery and contributes to decreasing the rate of cesarean sections.